Cold chain shipping mode choice with environmental and financial perspectives. (October 2020) - Zhang, Xiunian; Lam, Jasmine Siu Lee; Iris, Çağatay
Highlights: Increase environmental, operational and financial performances by optimizing mode choice and shipment planning. Value-Based Management is adopted for time sensitive (perishable) products. Shipment scheduling, different bulk chartering methods, ship speed and cargo depreciation are analyzed. Greenhouse gas emissions from cold chain shipping are evaluated. Optimal ship speed decreases with a higher decline rate when goods are less perishable. Abstract: Mode choice between reefer bulk and container in seaborne cold chains for time sensitive products is a practical problem, in which limited studies are available to guide decision makers. This study thoroughly investigates the cold chain mode choice problem by selecting shipping mode (containerized transport and bulk transport) for each shipment and determining shipment quantities and ship deployment in a multi-period planning environment with independent perishable product demands. Value-Based Management as a novel method in shipping is adopted to consider both economic and environmental objectives from operational and financial aspects. The value-based mode selection models also determine the sailing speed of the heterogeneous chartered reefer bulk fleet under different chartering terms. Furthermore, the paper evaluates greenhouse gas emissions from the cold chain shipping. Findings from a numerical example show that optimal ship speed decreases with a reducing rate when the bunker price increases and with a higher decline rate when goods are less perishable.